2018
DOI: 10.14202/vetworld.2018.459-463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Azolla feeding on the growth, feed conversion ratio, blood biochemical attributes and immune competence traits of growing turkeys

Abstract: Background and AimIn the recent past,few studies have been carried out in chicken to assess the effect of Azolla meal and raw Azolla feeding on the performance of chicken. If turkeys effectively use unconventional feedstuffs like Azolla without reducing the performance, it will increase the profitability of turkey business. Hence, a study was carried out to evaluate the effect of dried Azolla pinnata vis-a-vis raw Azolla as choice feeding on the growth, feed conversion ratio (FCR), blood biochemical attributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…The nutrient composition of azolla varies according to environmental conditions during cultivation ( 5 ). Furthermore, the ash percentages of SDAM, OM, and NFE were associated as reported by Shukla et al ( 31 ), who also found that an increased azolla rations, decreased OM content but increased CF this may be due to the higher total ash and CF content of azolla. In contrast, the percentage of CF of SDAM observed disagree with observations by Ara et al ( 32 ).…”
Section: Discussionsupporting
confidence: 75%
“…The nutrient composition of azolla varies according to environmental conditions during cultivation ( 5 ). Furthermore, the ash percentages of SDAM, OM, and NFE were associated as reported by Shukla et al ( 31 ), who also found that an increased azolla rations, decreased OM content but increased CF this may be due to the higher total ash and CF content of azolla. In contrast, the percentage of CF of SDAM observed disagree with observations by Ara et al ( 32 ).…”
Section: Discussionsupporting
confidence: 75%
“…Azolla is still cultivated in organically managed paddy fields, especially in rice-fish-Azolla or rice-duck-Azolla multi-ecoproduction systems in Asia (Cagauan, Branckaert, and van Hove 2000;Lu and Xia 2006;Cheng et al 2015). Additionally, Azolla has recently gained considerable importance for its multifaceted uses (Yadav et al 2014;Kollah, Patra, and Mohanty 2016;Shukla et al 2018;Chakraborty et al 2019). Use of Azolla as green manure can either be through its incorporation into paddy soil at the beginning of land preparation before rice transplanting or grown as a dual crop along with rice plants (Xu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Alalade and Iyayi [27] performed chemical analytical studies on the nutritional composition of Azolla meal and reported a presence of 21.4% crude protein, 12.7% crude fibre, 2.7% ether extract, 16.2% ash and 47.0% carbohydrate on DM basis with a gross energy value of 2039 kcal/kg. There were various reports on the usage of Azolla as feed supplement in livestock and poultry and its effect on body weight gain performance, immune condition, haematological and biochemical parameters [28][29][30][31][32]. This present paper deals the effect of feeding U. lactuca and Azolla as individual supplement and in combination on different performance parameters of Aseel chicken.…”
Section: Introductionmentioning
confidence: 99%